Resistance to Coal Transportation Policy in Jambi Province, Indonesia: What are the Causes? - Putra, Dinda; Yusuf, M.; Fatriani, Riri; Darminto, Citra; Hayati, Nazila (Talenta Publisher, 2025)
This study aims to identify the issues raised by the community in protesting coal transportation policies along the Trans-Sumatra Highway that passes through Jambi Province. Coal transportation along public roads often causes issues that interfere with community activities, ranging from traffic congestion and accidents to pollution and road damage. This study examines the issues that significantly impact social life along the Sumatra Trans-Road passing through Jambi Province. The study employs a literature review method, utilizing data from online news sources from 2023 to 2024, which were then analyzed using NVIVO 14. The results of this study indicate that each issue arising from coal transportation activities is interconnected, with traffic congestion and accidents being the most dominant, followed by road damage, community pressure for the completion of a dedicated coal road, and issues related to pollution and welfare.